Analisis Rasio Perpajakan Badan Usaha Sub Sektor Telekomunikasi Sebelum Dan Saat Covid-19 - Setiadi Alim Lim (BIP's JURNAL BISNIS PERSPEKTIF, 2022)
This study aims to examine whether there are differences in the profitability performance of the telecommunications sub sector business entities on the Indonesia Stock Exchange in the period before the occurrence of Covid-19 and during the occurrence of Covid-19. To measure the profitability performance used 12 taxation ratios and 2 other important profitability ratios. These ratios are calculated using data from the financial statements of telecommunication sub sector business entities on the Indonesia Stock Exchange in 2018-2021. For conditions prior to the occurrence of Covid-19, financial report data for 2018 and 2019 are used and for conditions during the occurrence of Covid-19, financial report data for 2020-2021 are used. The ratio data obtained were tested for normality using the Kolmogorov-Smirnov and Shapiro-Wilk methods. Ratios whose data before and during the occurrence of Covid-19 are normally distributed will be subjected to a Paired Samples T Test to determine whether there is a significant difference in values before and during the occurrence of Covid-19. Meanwhile, for ratios whose data are not normally distributed, the Wilcoxon Signed Rank Test is carried out to determine whether there is a significant difference in values before the occurrence of Covid-19 and during the occurrence of Covid-19. This study shows that there are 2 different ratios, namely Gross Profit Margin (GPM) and Rent/Sales (S/P) in the period before and during the Covid-19 outbreak. While the other 12 ratios are Pretax Profit Margin (PPM), Net Profit Margin (NPM), Corporate Tax to Turn Over Ratio (CTTOR), Operating Profit Margin (OPM), Return on Equity (ROE), Return on Assets (ROA), Depreciation/Sales (P/P), Interest/Sales (B/P), VAT/Sales (PPN/P), Salary/Sales (G/P), Non Operating Income/Sales (PLU/P), and Non Operating Expense/Sales (BLU/P) did not show any difference between before and during the Covid-19 outbreak.